1988
DOI: 10.1128/mcb.8.12.5448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T-cell antigen receptor-mediated transmembrane signaling by protein kinase C activation.

Abstract: The murine T-lymphoma cell line LBRM-33 is known to require synergistic signals delivered through the antigen receptor (T1-CD3) complex, together with interleukin 1 (IL-1), for activation of IL-2 gene expression and IL-2 production. Although 12-0-tetradecanoylphorbol-13-acetate (TPA) was capable of replacing IL-1 as an activating stimulus under certain conditions, biologic studies indicated that TPA failed to synergize with Ti-CD3-dependent stimuli under conditions in which IL-1 was clearly active. Acute expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
2
22
2
Order By: Relevance
“…While in both a murine T lymphoma line (9) and in neutrophils (7, 36) phosphorylation and down-regulation of receptors by PKC has been implicated, this observation cannot explain the effect of PMA on receptor-independent changes in [Ca 2ϩ ] i . Similarly, a reduction in IP 3 generated due to a PKCdependent phosphorylation of phospholipase C (9) fails to explain the observed reduction in release of Ca 2ϩ from internal stores following thapsigargin treatment (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…While in both a murine T lymphoma line (9) and in neutrophils (7, 36) phosphorylation and down-regulation of receptors by PKC has been implicated, this observation cannot explain the effect of PMA on receptor-independent changes in [Ca 2ϩ ] i . Similarly, a reduction in IP 3 generated due to a PKCdependent phosphorylation of phospholipase C (9) fails to explain the observed reduction in release of Ca 2ϩ from internal stores following thapsigargin treatment (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…It has been proposed that the decreased magnitude of agonist-stimulated changes in [Ca 2ϩ ] i after PMA pretreatment is due to a PKC-dependent phosphorylation and inactivation of phospholipase C (9). Such a phosphorylation would result in decreased production of IP 3 with a corresponding reduction in the amount of Ca 2ϩ released from the intracellular storage depot.…”
Section: Effects Of Phorbol Ester On Agonist-induced Changes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of protein b a s e C is associated with the transport of this enzyme from the cytosol to the plasma membrane [24]. Abraham et al showed, however, that IL 1 does not induce this process [25]. Thus, a difference in the biology of protein kinase C in these two clones is unlikely.…”
Section: Discussionmentioning
confidence: 95%
“…They act through high-affinity receptors but little is known of their post-receptor mechanisms. ILl causes no change in phosphoinositide breakdown, intracellular Ca 2+ or protein kinase C translocation in a T lymphoma line [3], although it does apparently increase breakdown of phosphatidylcholine (without affecting phosphatidylinositol) in Jurkat cells [4]. ILl does not change cAMP levels in fibroblasts and chondrocytes [5].…”
Section: Introductionmentioning
confidence: 99%